Pelayanan Pastoral di Era Modern dalam Memperkuat Spiritualitas Lansia di Panti Asuhan - Kowureng, Priskila; Jessica Elizabeth Abraham; Daeli, Natal Riang (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2024)
The purpose of this study is to explore and understand pastoral care can be more effective in helping the elderly in orphanages by implementing a holistic approach in accordance with the development of the times, as well as providing an understanding of how to overcome the limitations of traditional methods in pastoral care for the elderly in the modern era. The research method used is a qualitative approach, namely a literature study of e-books, journals, and books, related to the topic of discussion, and using an interview method involving the elderly, administrators, to gain deeper insight into the spiritual needs of the elderly. The results of the study indicate that pastoral care contributes positively to the spirituality of the elderly, increasing a sense of connectedness to the community and improving mental health, while the use of technology such as social media has proven effective in expanding the reach of services. The conclusion of this study is that pastoral care for the elderly in orphanages in the modern era is faced with significant challenges that require a more holistic and innovative approach. Traditional methods are considered inadequate to meet the complex emotional, social, and spiritual needs of the elderly, such as feelings of loneliness, isolation, and physical limitations. Therefore, this study emphasizes the importance of utilizing technology, such as video calls and digital platforms, to create deeper and more personal interactions.